The Becoming. (June 2015) - Sharpless, Joanna; Baldwin, Nell; Cook, Robert; Kofman, Aaron; Morley-Fletcher, Alessio; Slotkin, Rebecca; Wald, Hedy S.
<x xml:space="preserve">Abstract</x> Professional identity formation (PIF) within medical education is the multifaceted, individualized process through which students develop new ways of being in becoming physicians. Personal backgrounds, values, expectations, interests, goals, relationships, and role models can all influence PIF and may account for diversity of both experience and the active constructive process of professional formation. Guided reflection, including reflective writing, has been used to enhance awareness and meaning making within the PIF process for both students and medical educators and to shed light on what aspects of medical education are most constructive for healthy PIF. Student voices about the PIF process now emerging in the literature are often considered and interpreted by medical educators within qualitative studies or in broad theoretical overviews of PIF. In this Commentary, the authors present a chorus of individual student voices from along the medical education trajectory. Medical students (years 1–4) and a first-year resident in pediatrics respond to a variety of questions based on prevalent PIF themes extracted from the literature to reflect on their personal experiences of PIF. Topics queried included pretending in medical education, role of relationships, impact of formal and informal curricula on PIF (valuable aspects as well as suggestions for change), and navigating and developing interprofessional relationships and identities. This work aims to vividly illustrate the diverse and personal forces at play in individual students' PIF processes and to encourage future pedagogic efforts supporting healthy, integrated PIF in medical education.